Ovariectomy results in variable changes in nociception, mood and depression in adult female rats. - Li-Hong Li; Zhe-Chen Wang; Jin Yu; Yu-Qiu Zhang (PLoS ONE, 2014)
Decline in the ovarian hormones with menopause may influence somatosensory, cognitive, and affective processing. The present study investigated whether hormonal depletion alters the nociceptive, depressive-like and learning behaviors in experimental rats after ovariectomy (OVX), a common method to deplete animals of their gonadal hormones. OVX rats developed thermal hyperalgesia in proximal and distal tail that was established 2 weeks after OVX and lasted the 7 weeks of the experiment. A robust mechanical allodynia was also occurred at 5 weeks after OVX. In the 5th week after OVX, dilute formalin (5%)-induced nociceptive responses (such as elevating and licking or biting) during the second phase were significantly increased as compared to intact and sham-OVX females. However, chronic constriction injury (CCI) of the sciatic nerve-induced mechanical allodynia did not differ as hormonal status (e.g. OVX and ovarian intact). Using formalin-induced conditioned place avoidance (F-CPA), which is believed to reflect the pain-related negative emotion, we further found that OVX significantly attenuated F-CPA scores but did not alter electric foot-shock-induced CPA (S-CPA). In the open field and forced swimming test, there was an increase in depressive-like behaviors in OVX rats. There was no detectable impairment of spatial performance by Morris water maze task in OVX rats up to 5 weeks after surgery. Estrogen replacement retrieved OVX-induced nociceptive hypersensitivity and depressive-like behaviors. This is the first study to investigate the impacts of ovarian removal on nociceptive perception, negative emotion, depressive-like behaviors and spatial learning in adult female rats in a uniform and standard way.